Metabolic stress in patients with acute severe ulcerative colitis - a single-center cohort study - Redsted, Mathias; Grønhøj, Magnus; Brøchner, Louise Dalsgaard; Fassov, Janne; Svart, Mads Vandsted; Andersen, Jens Rikardt; Hvas, Christian Lodberg (Frontiers in Endocrinology, 2024)
Background and aims Acute severe ulcerative colitis (ASUC) is characterized by systemic inflammation, which may initiate an acute-phase response leading to hypercatabolism. Patients with ASUC are usually treated with high-dose steroids that may further accelerate the metabolic response and lead to hyperglycemia and insulin resistance. Nevertheless, the degree of synergy between inflammation and steroid treatment and their influence on the insulin resistance remains unknown. We aimed to measure the degree of metabolic stress including insulin resistance in patients with ASUC during admission and three weeks after discharge. Methods This single-center cohort study was conducted in adult patients with ASUC, defined and assessed by Truelove and Witt’s criteria. Indirect calorimetry, bioelectrical impedance analysis, and the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) were applied at baseline and at follow-up three weeks after discharge. Results Among the 22 patients admitted during the project period, 15 provided consent for participation in the study. Median C-reactive protein at inclusion was 37.6 [4; 154.7]. Both median HOMA-IR and fasting plasma glucose were markedly increased at inclusion (median 8.6 [3.8; 14.1] and 7.1 [6; 8.7], respectively), and both had decreased significantly three weeks after discharge (p=0.0036 and p=0.0039, respectively). No significant differences were observed in resting energy expenditure or anthropometric measurements from baseline to follow-up. Conclusion Patients with ASUC presented with marked insulin resistance, indicating that the days following admission and high-dose steroid treatment are particularly vulnerable. Despite improvement at three-week follow-up, patients still exhibited insulin resistance compared with relevant control groups. Clinical trial registration ClinicalTrials.gov, identifier NCT0527183.